Verdades e verdades: uma análise a partir do filme “A caça” - MADEIRO, Roseane Torres de (Universidade Federal do Rio de Janeiro, 2023)
This article aims to discuss the notion of truth to psychoanalysis in its interface with the law, for which the truth is sought in the facts through research; psychoanalysis, in turn, seeks to reveal the truth in the said subject. We will take the film The hunt (Jagten) because its plot is woven from the search for evidence of a fact allegedly occurred and based on the speech of a child, initially taken as truth. Thus, we question the practice of Testimony Without Damage, which consists of a survey with children, to establish the truth of the facts.